ANALISIS TERHADAP KEPEMIMPINAN PEREMPUAN DITINJAU DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM INDONESIA - Dedi Epriadi; Zuhdi Arman (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The cultural construction of women cannot be separated from the patriarchal ideology that considers men superior to women. Islam has made it clear that the goal of open Islam is to free humanity from all forms of injustice. And this is achieved by eliminating all forms of living systems that are tyrannical, repressive and discriminatory. Islam recognizes that they have different functions, but these differences do not necessarily lead to arbitrary differences or discrimination. Thus, the issue of women's leadership has also attracted the attention of scholars in Indonesia who have been involved in formulating problems and finding solutions from an Islamic perspective. The purpose of this study is to determine the position of women in Indonesian law and to determine whether female leadership in Indonesia is appropriate if it is linked to Islamic law. The method used in this study is qualitative and descriptive. The results show that the position of women in Indonesian law has so far occupied an important position before the law, and that the position of women in Islamic law is very noble, attracts enough attention and is in a very commendable position.